Institute of migration in the labor market: foreign experience and domestic realities - Druhova, Yevheniia (Global Prosperity, 2022)
The article draws attention to the need to consider global changes in the structure of employment when studying migration trends, causes, and consequences of labor market transformation. Social and economic aspects of intellectual migration from Ukraine are studied. Contradictions in the structure of labor supply in the labor market are outlined. The problem of the peculiarities of the development of the national economy due to the use of human capital is revealed, and the role of migration policy in it is assessed. The purpose of the research is to study the current trends in the development of migration processes in the world and in Ukraine in the context of the migration of human and intellectual capital in determining further directions of development. Research methodology: analysis and synthesis - when defining existing theories of migration, in particular in the context of intellectual capital as a separate type of migration; comparison and compilation – analysis of the previous global experience of migration processes; methods of scientific support - to summarize and formulate conclusions regarding the priority of the migration policy of Ukraine regarding the prevention of the consequences of migration. These approaches make it possible to characterize Ukraine’s challenges and opportunities for economic development, increasing the competitiveness of the country’s intellectual capital. It was concluded that the analysis of migration directions would ensure the predictability and orderliness of migration processes, and the development of an effective institutional field will create prerequisites for improving interstate and national regulation of migration flows.